A PARAMETRIC STUDY FOR FOUR NODE BILINEAR EAS SHELL ELEMENTS - Polat, Cengiz (Cambridge Univ Press, 2010)
A locking free formulation of 4-node bilinear shell element and its application to shell structures is demonstrated. The Enhanced Assumed Strain (EAS) method based on three-field variational principle of Hu-Washizu is used in the formulation. Transverse shear locking and membrane locking are circumvented by means of enhancing the displacement-dependent strain field with extra assumed strain field. Several benchmark shell problems are analyzed.
Keywords: Shell finite element; EAS method; Shear and membrane locking